2012
DOI: 10.1017/s1068280500001295
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Food Contamination on Brands: A Demand Systems Estimation of Peanut Butter

Abstract: A 2007 food-borne illness incident involving peanut butter is linked with structural change in consumer demand. Compensated and uncompensated own- and cross-price elasticities and expenditure elasticities were calculated for leading brands before and after the product recall using the Barten synthetic model and weekly time-series data from 2006 through 2008. Statistically significant differences in price elasticities for the affected brand, Peter Pan, were absent. After a period of 27 weeks, this brand essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…The present study differs from the earlier study of Bakhtavoryan, Capps, and Salin (2012) in a few aspects. First, in the current study, the analysis of competition was done from the perspective of brands responding to the Peter Pan recall based on the outbreak variable as an information source about the recall.…”
Section: Literature Reviewcontrasting
confidence: 92%
See 3 more Smart Citations
“…The present study differs from the earlier study of Bakhtavoryan, Capps, and Salin (2012) in a few aspects. First, in the current study, the analysis of competition was done from the perspective of brands responding to the Peter Pan recall based on the outbreak variable as an information source about the recall.…”
Section: Literature Reviewcontrasting
confidence: 92%
“…The manner in which consumers receive information about the likelihood of harm influences their purchase decisions and is a key issue in the empirical research on impact of safety events. Some studies establish a comparison of consumer demand before and after an event (Bakhtavoryan, Capps, and Salin, 2012;Cawley and Rizzo, 2005) under the hypothesis that once an event occurs, there is a "structural change" in the demand because of the new information. Others take into account the possibility that consumers' reaction takes time or can build over time as more people become aware because of psychological, technological, and institutional reasons (Griliches, 1967).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease and other contamination incidents potentially leading to unsafe food products can cause a significant decline in consumer demand and substantial losses in sales, both for the contaminated product and for the uncontaminated products that are close substitutes. This has been documented in a number of studies for various foods (Bakhtavoryan, Capps, and Salin, 2012;Burton and Young, 1996;Fousekis and Revell, 2004;Piggott and Marsh, 2004;Pritchett et al, 2007;Uchida, Roheim, and Johnston, 2017;Verbeke and Ward, 2001), as well as specifically for salmon (Liu, Lien, and Asche, 2016;Sha et al, 2015). Several studies have also demonstrated a country-of-origin effect for 1 One example of a large disaster with limited impact on the seafood market is the Fukushima accident (Wakamatsu and Miyata, 2016).…”
Section: Introductionmentioning
confidence: 93%